A Chlorinated Donor Polymer Achieving High‐Performance Organic Solar Cells with a Wide Range of Polymer Molecular Weight. (16th June 2021) - Zeng, Anping; Ma, Xiaoling; Pan, Mingao; Chen, Yuzhong; Ma, Ruijie; Zhao, Heng; Zhang, Jianquan; Kim, Ha Kyung; Shang, Ao; Luo, Siwei; Angunawela, Indunil Chathurangani; Chang, Yuan; et al.
Abstract: In the field of non‐fullerene organic solar cells (OSCs), compared to the rapid development of non‐fullerene acceptors, the progress of high‐performance donor polymers is relatively slow. The property and performance of donor polymers in OSCs are often sensitive to the molecular weight of the polymers. In this study, a chlorinated donor polymer named D18‐Cl is reported, which can achieve high performance with a wide range of polymer molecular weight. The devices based on D18‐Cl show a higher open‐circuit voltage ( V OC ) due to the slightly deeper energy levels and an outstanding short‐circuit current density ( J SC ) owing to the appropriate long periods of blend films and less ([6, 6]‐phenyl‐C71‐butyric acid methyl ester) (PC71 BM) in mixed domains, leading to the higher efficiency of 17.97% than those of the D18‐based devices (17.21%). Meanwhile, D18‐Cl can achieve high efficiencies (17.30–17.97%) when its number‐averaged molecular weight ( M n ) is ranged from 45 to 72 kDa. In contrast, the D18‐based devices only exhibit relatively high efficiencies in a narrow M n range of ≈70 kDa. Such property and performance make D18‐Cl a promising donor polymer for scale‐up and low‐cost production. Abstract : In this study, a chlorinated polymer named D18‐Cl is designed and synthesized, leading to highly efficient (near 18%) organic solar cells, yet whose performance is insensitive to its molecular weight. These advantages make D18‐Cl a more promising donor polymer than previously reported polymer D18 for scale‐up and low‐cost production.